Is there a bias in patient choices for hospital care? Evidence from three Italian regional health systems. Issue 7 (July 2022) - Martini, Gianmaria; Levaggi, Rosella; Spinelli, Daniele
Highlights: We study patients preferences for surgery across Italian regional health care systems. We find region-dependent biases towards best performers in patient choice. Institutional setting plays a relevant role in patients' substitution patterns. Patients' awareness for clinical quality is higher in a competitive setting. Less competitive settings require stricter regulation and control of quality indicators. Abstract: Patients choice is at the core of competition in hospital care. In spite of a flourishing literature, little is known about the true process leading patients to choose a specific provider. Most models in this literature assume - without testing - that hospitals are perceived to be homogeneous providers. In this article we take a different direction. We assume that patients have a bias towards some types of hospitals, we test this hypothesis and show which attributes determine this bias. We exploit the characteristic of Italian health care organization, where devolution has allowed regional systems to choose the level of competition and the private-public hospitals mix. We estimate conditional logit models for hip replacement admissions in three regions (Lombardy, Veneto, and Emilia-Romagna) over the period 2014- 2016. We show that, depending on the competition framework (peculiar to each region) patients are aware that some hospitals are best performers in their area and are willing to travel more to be admitted there. This is particularly true for regional health care systems where competition between public and private providers is well developed. Our model provides interesting policy implications: a) the idea that hospitals are different in patients perception should be kept in mind in the architecture of the market for hospital care; b) clinical quality as a driver to patients choice seems to work better in a less regulated competition settings